The Use of Celestial Bodies to Build Self-esteem in Your Soul is a River - Parwoto, Endah Triwigati; Itsna Syahadatud Dinurriyah, MA (Alphabet, 2024)
This research aims to show the use of celestial bodies to build self-esteem, specifically within the chapter The Cosmos from the poetry book Your Soul is a River. The poems discussed are You Are the Sun; You Matter; Who You Are, What You Are Not; Beautiful and Terrible Things, which are considered as the research objects, appropriate to the objective of this research. This group of research object has the same theme, that is celestial bodies. In analyzing these poems, this study employs Wolfgang Iser's implied reader, which focuses on the reading process, emphasizing the understanding and interpretation of the celestial bodies in the poems to build self-esteem. This study uses a qualitative descriptive research method, which includes content analysis of the textual material. This research discusses the interpretation of celestial bodies in the poems and the influence of celestial bodies to build self-esteem. The study finds that each celestial object in the poems mainly carries meaning relating to self-confidence, self-acceptance, personal growth, and human experience, serving as a powerful source of inspiration for positive self-reflection and personal growth, which helps someone feel better about their self-esteem.